2009
DOI: 10.1111/j.1745-4514.2009.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Solubility and Production of Gels From Jumbo Squid

Abstract: Solubility at several ionic strengths (0 to 1.0 M), pH (2 to 13) and gelling capacity of jumbo squid Dosidicus gigas muscle proteins were evaluated. Protein recovery was >90% at pH 9–12. Autohydrolysis was evaluated and affected only sarcoplasmic proteins. Folding score was 5 on all gels. Strength was higher for thermal gels prepared from squid fin (50.2 ± 1.2 N) than that prepared from the mantle (23.4 ± 2.5 N). There was no significant difference in gel strengths from previously frozen (46.4 ± 7.5 N) and nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Electrophoresis profile of uncooked squid muscle analyzed in this work tend to be similar than previous reported by Ezquerra‐Brauer, Haard, Ramírez‐Olivas, Olivas‐Burrola, and Velázquez‐Sánchez () on ice‐storage mantle muscle. Furthermore, Fuente‐Betancourt, García‐Carreño, Navarrete del Toro, Córdova‐Murueta, and Lugo‐Sánchez () produced proteins gels from squid mantle muscle that also share comparable electrophoresis pattern than registered in our results. Moreover, Raman and Mathew () studied protein physicochemical and structural changes of cooked (at different heating temperatures) mantle muscle from Indian squid ( Loligo duvauceli ); these authors reported protein denaturation and formation of new low molecular weight proteins as evidenced in SDS‐PAGE of pre‐fractionated proteins.…”
Section: Resultssupporting
confidence: 78%
“…Electrophoresis profile of uncooked squid muscle analyzed in this work tend to be similar than previous reported by Ezquerra‐Brauer, Haard, Ramírez‐Olivas, Olivas‐Burrola, and Velázquez‐Sánchez () on ice‐storage mantle muscle. Furthermore, Fuente‐Betancourt, García‐Carreño, Navarrete del Toro, Córdova‐Murueta, and Lugo‐Sánchez () produced proteins gels from squid mantle muscle that also share comparable electrophoresis pattern than registered in our results. Moreover, Raman and Mathew () studied protein physicochemical and structural changes of cooked (at different heating temperatures) mantle muscle from Indian squid ( Loligo duvauceli ); these authors reported protein denaturation and formation of new low molecular weight proteins as evidenced in SDS‐PAGE of pre‐fractionated proteins.…”
Section: Resultssupporting
confidence: 78%
“…However, the gel produced from fins is reported to have more gel strength value than that of gel produced from mantle only. [64] The gel strength value of fresh white leg shrimp was 80.60 g.cm. The gel produced from white leg shrimp was very fragile and bearing pink colour.…”
Section: Gel Strengthmentioning
confidence: 96%
“…They have some advantages including its color, low fat content, mild flavor, and the y represent an abundance of underutilized species. Despite the fact that acceptable collagen‐based edible gels can be obtained as reported by De La Fuente‐Betancourt and others (2009), the traditional method to make surimi cannot be applied to cephalopod muscle. Its myofibrillar protein is much more water‐soluble than fish muscle, with some odorous compounds, and its high protease activity cause decreased functionality of the obtained product (Izquierdo‐Jiménez and others 2003; Careche and Borderías 2004; Sánchez‐Alonso and others 2007a; De La Fuente‐Betancourt and others 2009).…”
Section: Surimi From Underutilized Speciesmentioning
confidence: 99%